(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Introduzione - 2. Vivere al tempo dei “divieti”, con i temperamenti della Corte costituzionale - 3. Edifici, luoghi, spazi - 4. Un’architettura “scomposta”: dal minareto di cristallo all’area per la moschea destinata a parcheggio. Secularism and Right to the Building of Worship ABSTRACT: Article 19 of the Italian constitution guarantees the right to worship as one of the three subjective public rights, together with the right to profess one’s own creed and propagate it, through which religious freedom is manifested. However, people belonging to certain religions face obstacles in having places where they can perform their rituals. Particularly, the request to build mosques on Italian soil encounters many denials, especially of a legislative nature. The essay analyzes, also through the reference to concrete cases, the problems in the field and proposes to reflect on the concept of space where people can develop their personality and fulfill the mandatory duties of political, economic and social solidarity.